Feasibility Study on Discrimination of Neo-plastic and Non-Neoplastic Gastric Tissues Using Spark Discharge Assisted Laser Induced Breakdown Spectroscopy - Seifalinezhad, Aida; Bahreini, Maryam; Hassani Matin, Mohammad Mahdi; Tavassoli, Seyed Hassan (Journal of Lasers in Medical Sciences, 2018)
Introduction: The present work is a novel in vitro study that evaluated the possibility of diagnosing neoplastic from nonneoplastic gastric tissues using spark discharge assisted laser induced breakdown spectroscopy (SD-LIBS) method. Methods: In these experiments, the low energy laser pulses ablated a tiny amount of tissue surface leading to plasma formation. Then, a spark discharge was applied to plasma in order to intensify the plasma radiation. Light emission from plasma was recorded as spectra which were analyzed. Gastric tissues of 5 people were studied through this method. Results: The SD-LIBS technique had the potential to discriminate normal and cancerous tissues based on the significant differences in the intensities of some particular elements. The comparison of normalized calcium (Ca) and magnesium (Mg) peaks of neoplastic and nonneoplastic gastric tissues could be viewed as a practical measure for tissue discrimination since Ca and Mg peaks in spectra of neoplastic were noticeably higher than nonneoplastic. Conclusion: Considering the identification of gastric cancer, the applied method in these experiments seems quite fast, noninvasive and cost-effective with respect to other conventional methods. The significant increment of specific Ca and Mg lines of neoplastic gastric tissues in comparison to the nonneoplastic ones can be considered as valuable information that might bring about tissue classification. The number of samples in this work, however, was not sufficient for a decisive conclusion and further researches is needed to generalize this idea.